Quasi-spin projection in an exactly soluble model - Cambiaggio, María Cristina (1979)
An exactly soluble model for the study of projection techniques within the framework of the Hartree-Fock theory is presented. Properties of the exact solutions are analyzed and projections, both before and after variation, are discussed.